Projected Prevalence of Inadequate Nutrient Intakes in Europe - Viñas, Blanca Roman; Roman Viñas, Blanca; Barba, Lourdes Ribas; Ribas Barba, Lourdes; Ngo, Joy; Gurinovic, Mirjana; Novakovic, Romana; Cavelaars, Adriënne; de Groot, Lisette C. P. G. M.; van't Veer, Pieter; Matthys, Christophe; Majem, Lluís Serra; et al. (Annals of Nutrition and Metabolism, 2011)
Background: The purpose of this study was to analyze the prevalence of nutrient intake inadequacy in Europe, applying the Nordic Nutritional Recommendations in the context of the EURRECA Network of Excellence. Methods: Nutrient data was obtained from the European Nutrition and Health Report II. Those nutritional surveys using a validated food frequency questionnaire or diet history and a food diary/ register with at least 7 days of registers or with an adjustment for intraindividual variability were included. The nutrients analyzed were: vitamin C, vitamin D, vitamin B12, folic acid, calcium, iron, zinc, selenium, copper, and iodine. The estimated average requirement cut point was applied to estimate inadequacy. The Nordic and Institute of Medicine nutrient recommendations were used as references. Results: The mean prevalence of inadequacy was below 11% for zinc, iron, and vitamin B12 (only in the elderly), and it was 11–20% for copper in adults and the elderly and for vitamin B12 in adults and vitamin C in the elderly. The prevalence was above 20% for vitamin D, folic acid, calcium, selenium, and iodine in adults and the elderly and for vitamin C in adults. Conclusions: Vitamin C, vitamin D, folic acid, calcium, selenium, and iodine were the nutrients showing a higher prevalence of inadequate intakes in Europe.